Rationalizing National Government Subsidies for State Universities and Colleges - Rosario G. Manasan (Philippine Institute for Development Studies (PIDS), 2012)
This study aims to review and assess (i) the sources and uses of funds of state universities and colleges (SUCs); (ii) the impact of the application normative funding formula (NFF) for SUCs; and (iii) the utilization of the Higher Education Development Fund (HEDF) with the end in view of rationalizing the allocation of national government funding of SUCs by improving the effectiveness in the use of public funds for higher education and by increasing the efficiency of SUCs spending.The study found that while the application of the normative funding formula has clearly resulted in the SUCs' greater reliance on internally generated income, the implementation of the NFF has not exhibited the desired effect on (i) shifting SUCs enrollment toward priority courses; and (ii) improving the quality of instruction.On the other hand, the study's inquiry into the major cost drivers of SUCs provision of higher education indicates that there are economies of scale in the SUC sector that can be harnessed. This finding supports proposals for the amalgamation of SUCs. Also, the multiplicity of program offerings among SUCs is found to push SUCs' per student cost upwards. The number or the proportion of faculty members who are MS/PhD degree holders are likewise found to have a significant influence on per student costs. In contrast, the analysis also reveals that the number of satellite campuses and the size of SUCs enrollment in MS/PhD programs are not good determinants of per student costs.The study also looked into the determinants of the quality of education provided by SUCs (as proxied by the passing rate in licensure examinations). The analysis reveals that the number of faculty with MS/PhD degrees and the number of centers of developments (CODs) both have positive and statistically significant relationship with the passing rate in licensure examinations. Surprisingly, per student cost is not found to have statistically significant influence on the licensure examinations passing rate. This result suggests that there is some scope for reducing per student cost without necessarily affecting the quality of education provided by SUCs.
Keywords: 330; economies of scale; Philippines; cost efficiency; state universities and colleges (SUCs); income-generating projects (IGPs); normative funding formula (NFF); quality of instruction; scholarships; Hochschulfinanzierung; Effizienz; Skalenertrag; Philippinen